PENGELOLAAN PEMBELAJARAN DI KB TUNAS HARAPAN KABUPATEN SUMENEP - Triana Rosalina Noor; Faizah (IAI DARUL ULUM KANDANGAN, 2024)
The aim of this research is to describe the management of early childhood education (PAUD) learning based on processes of planning, organizing, implementing, and monitoring. The research approach used qualitative case study at KB Tunas Harapan, Sumenep Regency. By utilizing document study techniques, observation, and interviews with the foundation chairman, school principal, and teachers. The data obtained are analyzed descriptively through stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that KB Tunas Harapan manages learning through several stages. In the learning planning process, the school pours it into annual, semester, weekly, and daily activity plans. In organizing, KB Tunas Harapan assigns tasks to personnel to be responsible for implementing the grouping of prepared materials. In the implementation process, KB Tunas Harapan students' learning is carried out using various methods of delivery, from storytelling to question and answer, while still referring to the planned materials. In the monitoring process, KB Tunas Harapan involves the school principal and the foundation chairman through comparing achievement evaluations with the established plans. If there is any failure to achieve, corrective action will be taken as a basis for improvement in the learning process in the following year.